Economical Order Quantity, Safety Stock dan Reorder Point pada Raw Inventory - Juniaty Ismail (Jurnal Akuntansi dan Audit Syariah)
This research was conducted with the aim to find out how the management of inventories of raw materials in UKM FM in times of scarcity and rising raw material prices. The difference between this study and previous studies is that the focus of the research is on small and medium enterprises that do not understand how to properly manage raw materials. In this study the authors were directly involved in the observation and interview, so that the data collected is completely accurate according to research needs. The steps of data collection including observation, interviews and documentation. The data analysis technique used is descriptive qualitative method with EOQ analysis. The results showed that UKM FM in producing its products primarily shredded fish often run into obstacles that the scarcity of raw materials of fish when the weather is bad, so the level of demand for such raw materials as well as production processes become inhibited. Moreover, scarcity of raw materials that contributed to rising prices of raw materials and consequently also influence the selling prices come down in consumer demand. To overcome this, the UKM FM do it with EOQ Analysis, Safety Stock and Reorder Point approach.